Pengaruh Program Bantuan Pangan Non Tunai (BPNT) terhadap Kesejahteraan Keluarga Miskin - Putri Regina C. Da’ada; Roy Hasiru; Rierind Koniyo; Melizubaida Mahmud; Yulianti Toralawe (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study is motivated by the disparity in welfare outcomes and the level of dependency among beneficiaries, where most Beneficiary Families (KPM) of the Non-Cash Food Assistance (BPNT) program in Biontong Village still experience relatively low income levels and high dependency on the program. This indicates that BPNT has not yet provided a significant and sustainable impact on improving the welfare and independence of poor households. The objective of this study is to analyze the effect of the BPNT program on the welfare of poor families in Biontong Village, Bolangitang Timur District, North Bolaang Mongondow Regency. This research employs a quantitative approach using questionnaires as the primary data collection method. The sample consists of 72 respondents who are BPNT beneficiaries, and the data are analyzed using simple linear regression. The results reveal a positive and significant effect of BPNT on the welfare of poor families. This is evidenced by a significance value of 0.000 < 0.05 and a t-value of 4.614 exceeding the t-table value of 1.667, indicating that the alternative hypothesis is accepted. These findings suggest that BPNT contributes to welfare improvement, although it has not fully reduced long-term dependency.